Significance of Hydrogen Sulfide Production in the Pancreatic β-Cell - Shigeki Taniguchi; Ichiro Niki (Elsevier, 2011)
Abstract.: Hydrogen sulfide (H2S) is an important signaling molecule in various mammalian cells and tissues. H2S is synthesized from l-cysteine and regulates several cellular and physiological phenomena (vasorelaxation, hormone secretion, and apoptosis) and multicellular events (neuro modulation and inflammatory responses). H2S can be produced in pancreatic β-cells by cystathionine β-synthase (CBS) or cystathionine γ-lyase (CSE). H2S inhibits insulin release and regulates β-cell survival. We found that glucose stimulation increased CSE expression at transcript and protein levels in mouse pancreatic islets. We also found that H2S protects β-cells that were chronically exposed to high glucose from apoptotic cell death. Loss of β-cell mass and failures of β-cell function are important in the pathogenesis and/or progression of diabetes mellitus; therefore, molecular analyses of the mechanisms of H2S production and its protective effects on β-cells may lead to new insights into diabetes mellitus. Keywords:: hydrogen sulfide, gasotransmitter, pancreatic β-cell, cytoprotection, diabetes mellitus